2019
DOI: 10.1021/acssensors.9b00882
|View full text |Cite
|
Sign up to set email alerts
|

3D Hollow Quasi-Graphite Capsules/Polyaniline Hybrid with a High Performance for Room-Temperature Ammonia Gas Sensors

Abstract: Designing sensing materials with novel morphologies and compositions is eminently challenging to achieve high-performance gas sensor devices. Herein, an in situ oxidative polymerization approach is developed to construct three-dimensional (3D) hollow quasi-graphite capsules/polyaniline (GCs/PANI) hierarchical hybrids by decorating protonated PANI on the surface of GCs; as a result, an immensely active and sensitive material was developed for sensing ammonia gas at room temperature. Moreover, the GCs possessed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 43 publications
0
40
0
Order By: Relevance
“…Some studies have shown that iron can promote the graphitization of sp 2 carbon and adjust the electronic state of the sp 2 carbon [31,32]. The graphitization of carbon is also conducive to the electron transfer of the catalyst and solidifies the nano-catalyst to reduce the agglomeration of the catalyst [25,33], and all these advantages make it have an excellent ORR activity. It has also been found that the catalytic activity of Fe-based compounds is directly related to the size of the materials [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that iron can promote the graphitization of sp 2 carbon and adjust the electronic state of the sp 2 carbon [31,32]. The graphitization of carbon is also conducive to the electron transfer of the catalyst and solidifies the nano-catalyst to reduce the agglomeration of the catalyst [25,33], and all these advantages make it have an excellent ORR activity. It has also been found that the catalytic activity of Fe-based compounds is directly related to the size of the materials [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of PANI and NiO in our synthesized hybrid composite were further demonstrated by the RAMAN spectra shown in figure 2. For PANI the peaks at 416, 522, 573, 775, 1167, 1218, 1409, 1495 and 1605 cm −1 were observed and assigned to out of plane C−H wagging, deformation of polaronic amine, deformation of bipolaronic amine, C−H out of plane bending of quinoid ring, C−H bending of quinoid ring, C−N stretching vibration of cationic radical species, C−N + stretching vibration of cationic radical species, C=N stretching of quinoid ring, C−C stretching vibration of quinoid ring [28–33] …”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18][19][20][21][22] All these studies contributed to scaling up production of sustainable, efficient and cost-effective quality G sheets. [23][24][25] Innovative methods such as electrochemical reduction of exfoliated G oxide (GO) (which is oxidative and water-soluble form of G), 5 epitaxial growth in GP or in metals via chemical vapor deposition (CVD), facilitated this production [26][27][28][29][30][31][32] ( Figure 4). In particular, G have excited many researchers and industrials interested in developing nanobiosensors since Sir Geim and Sir Novoselov were awarded the 2010 Nobel Prize in Physics.…”
Section: Introductionmentioning
confidence: 99%